Economics of energy storage in a residential consumer context - João Tomé Saraiva (2016)
With the increase of electricity tariffs and the decreasing costs for distributed generation technologies, more and more residential consumers are deploying local generation systems to satisfy their electricity demand in order to reduce overall cost. Typically, however, a mismatch between electricity generation and demand remains. Storage systems enable consumers to reduce this mismatch by storing locally generated electricity for later consumption, instead of feeding excess generation into the grid. This paper analyzes the economics of storage installations in a residential consumer context. A linear program is presented to determine the optimal dispatch, and Simulated Annealing is used to identify the cost minimizing system configuration. The developed approach is tested for a multi-family house in Germany.